Muslim Population Share, Religious Demography, and Economic Development Patterns in Muslim-Majority Countries: A Cross-Country Exploratory Study - Lathif Hanafir Rifqi; Musahadi Musahadi; Muchlis Yahya; Ana Zahrotun Nihayah; Tanjeel Ahmed; Siti Mujibatun (Shirkah: Journal of Economics and Business, 2026)
This study examines the relationship between Muslim population share and selected development indicators in Muslim-majority countries through a non-causal, exploratory cross-country approach. Using secondary data from 44 Muslim-majority countries (2019–2024), this study examines statistical associations between religious demography and three development indicators: per capita income, income inequality (Gini index), and Human Development Index (HDI), using data obtained from the Pew Research Center, the World Bank, and United Nations Development Program (UNDP), ensuring comparability and reliability across countries. The data were analyzed through Pearson correlation to determine associations among variables. The findings reveal moderate negative associations between Muslim population share and both per capita income and HDI, whereas the relationship with income inequality appears weak and statistically insignificant. However, the results do not support causal interpretations, as considerable heterogeneity exists across countries with similar religious demographic compositions. These findings suggest that development outcomes in Muslim-majority countries are shaped more by institutional and structural factors than by religious demography alone, emphasizing the importance of a broader macro-level understanding of religion–development linkages